Two-photon excited red-green "discoloration" bioprobes for monitoring lipid droplets and lipid droplet-lysosomal autophagy. Issue 14 (22nd March 2023) - Liu, Ming-Xuan; Xu, Li; Zhu, Peng-Fei; Li, Xin; Shan, Miao; Jin, Wei; Chen, Jing; Ling, Yong; Zhang, Xiao-Ling
Abstract : DPABP-BI is the first two-photon excited organic molecule which can simultaneously recognize LDs and monitor their autophagy process via different fluorescence emission colors. Abstract : Lipid droplets (LDs) and their autophagy by lysosomes are closely related to a variety of physiological and pathological conditions. Therefore, identifying and tracking LDs and the dynamic process of autophagy can provide useful information for the diagnostics and treatment of related diseases. However, few organic small molecule-based fluorescent probes can specifically recognize LDs and dynamically track their autophagy process. Herein, we synthesized a "discoloration" fluorescent bioprobe DPABP-BI with distinguishable features including red fluorescence emission (630 nm), large Stokes shift (145 nm), two-photon excitation and outstanding photostability and biocompatibility. In particular, LDs could be specifically identified via the red fluorescence emission of DPABP-BI (colocalization constant of 0.98), while autophagolysosomes could be visualized via the green fluorescence emission of its acid-hydrolyzed product (colocalization constant of 0.90) to track the autophagy dynamic process. In addition, DPABP-BI enabled the specific recognition of fatty substances in zebrafish larvae. In this study, a two-photon excited red light small molecule probe was constructed to identify LDs and track their autophagy dynamic process by changing the fluorescence emission wavelength.